Comorbid Conditions and Social Determinants of Smoking in an Adult Population - Aydın Güçlü, Özge; Acet Öztürk, Nilüfer Aylin; Görek Dilektaşlı, Aslı; Demirdöğen, Ezgi; Karadağ, Mehmet; Uzaslan, Esra (Addicta: The Turkish Journal on Addictions, 2020)
Tobacco smoking is a significant risk factor for a variety of chronic disorders, such as chronic obstructive pulmonary disease (COPD), lung cancer, cardiovascular diseases, and other forms of malignancies. In this study, we investigated the comorbid medical conditions and sociodemographic features that contribute to disparities in tobacco smoking prevalence in the adult population. We included volunteers who participated in events for the “World COPD day” in 4 consecutive years (i.e., 2014, 2015, 2016, and 2017) held in Bursa, Turkey. Sociodemographic features, smoking characteristics, and comorbidities were recorded. A total of 747 volunteers who were 47.1±14.5 [16-84] years of age and smoked 24.1±20.91 pack-years were included. The study population consisted of 405 (54.2%) males, 36.3% of which were current smokers, 23.6% ex-smokers, and 40.2% nonsmokers. Moreover, 15.7% of participants with asthma were nonsmokers and 9.4% ever-smoker (p=0.011), while 2% of participants with coronary artery disease (CAD) were nonsmoker and 6.7% were ever-smoker (p=0.003). Current smoker participants exhibited more symptoms such as cough, sputum, and wheezing (p